Analisis Pengaruh Perlakuan Panas Terhadap Sifat Kekerasan Baja Karbon S55C - Rohman, Fathur; Yudo, Eko; Yuliyanto, Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to analyze the effect of the heat treatment (quenching) process on the hardness of S55C carbon steel used as cutting blades for plastic shredding machines. JIS S55C steel was chosen as an alternative material, with hardening temperature variations of 850°C, 950°C, and 1050°C, and cooling media consisting of well water, young coconut water, and cooking oil (3 liters each). The test results showed that the hardness of the steel before heat treatment was 29.6 HRC. After heat treatment, the highest hardness was achieved at a temperature of 950°C with a value of 56 HRC using well water as the cooling medium. This study concludes that temperature variations and cooling media significantly influence the hardness of S55C steel.